2000
DOI: 10.1080/10439463.2000.9964851
|View full text |Cite
|
Sign up to set email alerts
|

Violence in the night‐time economy; bouncers: The reporting, recording and prosecution of assaults1

Abstract: This paper, based on ethnographic research, is concerned with the accountability of licensed premise door staff -better known as 'bouncers'. 2 The situational dynamics of the bouncer's enacted environment ensures that theirs is a role consistently exposed to the interactions of violence. As such, allegations of assault, both upon and by door staff, are common. This paper reports upon incidents of door staff violence and why they often fail to be investigated and, when they are investigated, why they frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 6 publications
0
49
0
Order By: Relevance
“…Hope (1986) reported one quarter of police-attended incidents in one study occurred within a 250 square metre area containing 12 pubs and that offences peaked between 11.00pm and 11.30pm. Lister et al (2000) found 29% of violent offences occurred inside licensed premises and 70% of city centre violence took place between 9.00pm and 3.00am. Hutchinson et al (1998) compiled evidence from 163 Accident and Emergency (A&E) departments in England and Wales and reported that 90% of facial injuries in pubs and bars, and 45% of facial injuries incurred in the street were associated with alcohol consumption.…”
Section: Alcohol-related Violencementioning
confidence: 99%
“…Hope (1986) reported one quarter of police-attended incidents in one study occurred within a 250 square metre area containing 12 pubs and that offences peaked between 11.00pm and 11.30pm. Lister et al (2000) found 29% of violent offences occurred inside licensed premises and 70% of city centre violence took place between 9.00pm and 3.00am. Hutchinson et al (1998) compiled evidence from 163 Accident and Emergency (A&E) departments in England and Wales and reported that 90% of facial injuries in pubs and bars, and 45% of facial injuries incurred in the street were associated with alcohol consumption.…”
Section: Alcohol-related Violencementioning
confidence: 99%
“…Hope (1986) found one quarter of police-attended incidents (including violence) in Newcastle-upon-Tyne city centre occurred within a 250 square metre area containing 12 pubs with a peak in offences from 11.00pm to 11.30pm. Lister et al (2000) found that 29 per cent of recorded violent incidents in Eastville occurred inside licensed premises, and 70 per cent of city centre violence occurred between 9.00pm and 3.00am. Thus there has been an increased focus and shift towards areas with concentrations of NTE activity.…”
Section: The Focus On the Nte Environmentmentioning
confidence: 99%
“…Finally, the bias of using bouncers to collect data also represents a limitation, as they may have failed to report some aggressive incidents committed or instigated by staff (Graham et al 2005;Wells et al 1998). Nevertheless, bouncers likely provided more insight than would have outside observers (Calvey 2000;Lister et al 2000;Monahagan 2004;Hobbs et al 2002;Hobbs 2003;Winlow et al 2001). …”
Section: Study Limitationmentioning
confidence: 99%
“…Studies that have utilized bouncer-ethnographers or "covert methodology" have demonstrated that this design provides an in-depth understanding of what really happens in clubs while revealing facts that would not otherwise be distinguishable for outsiders or through official data (Hobbs 2003;Hobbs et al 2002;Lister et al 2000;Monahagan 2004;Winlow et al 2001). The co-author acting as a "bouncer ethnographer" was an employee of the nightclub during data collection.…”
Section: Data Collectionmentioning
confidence: 99%